KOMUNIKASI INTERPERSONAL GURU DALAM MEMOTIVASI BELAJAR SISWA DI SEKOLAH DASAR NEGERI 28 MANDAU KABUPATEN BENGKALIS - Sari, Nadya Devita; Susanti, Hevi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
SDN 28 Mandau, located at Hangtuah Street No.21, Batang Serosa, Mandau District, Bengkalis Regency, Riau Province, faces challenges in student learning motivation. Some students exhibit low learning motivation, reflected in their unsatisfactory academic performance. Despite the school's efforts to improve the quality of education, such as enhancing facilities, upgrading teacher quality, and organizing extracurricular activities, these measures have not fully addressed the issue. To tackle this problem, teachers have started implementing interpersonal communication in their interactions with students. This study focuses on how aspects of interpersonal communication such as openness, empathy, support, positive attitude, and equality demonstrated by teachers can affect student learning motivation at SDN 28 Mandau. This research is crucial because low learning motivation can negatively impact students' academic and character development. The study aims to analyze how the openness, empathy, support, positive attitude, and equality teachers provide to students and their parents during the learning process at SDN 28 Mandau can influence student learning motivation. This study used a qualitative research method with a descriptive approach. The subjects of this research were teachers, students, and parents of students at SDN 28 Mandau, selected using a purposive sampling technique. Data collection techniques included observation, interviews, and documentation. The analysis technique used was the Miles and Huberman model. To ensure data validity, this study utilized extended participation and triangulation. The study results showed that the interpersonal communication at SDN 28 Mandau was very effective. The openness of the teachers created a positive environment for the students and their parents, where teachers ga ve students the opportunity to participate in class discussions without discrimination actively. Teachers also show empathy by understanding students' personal or academic challenges and providing appropriate support and solutions. Active support from teachers was also evident in their visits to the homes of students who frequently missed school to communicate with parents, offer assistance, and plan strategies to boost students' motivation to learn. The positive attitude of teachers was reflected in the form of recognition and praise for students who achieved accomplishments, which helped boost their motivation and self-confidence. Equality in interactions between teachers and students was evident in their joint participation in sports activities outside of class hours, fostering closer relationships and supporting positive learning experiences at school. The results of this study can serve as a guide for SDN 28 Mandau in efforts to enhance student learning motivation